Community based interventional study on dengue awareness and vector control in a rural population in Ernakulam, Kerala - George, Leyanna Susan; S., Aswathy; Paul, Nimitha; Leelamoni, K. (International Journal Of Community Medicine And Public Health, 2017)
Background: Dengue fever is an acute infectious disease for which there are currently no specific drugs or effective vaccines available. Therefore its prevention & control solely rest on vector control strategies, for which behavioural change of the community is a requirement. Hence, the aim of our study was to implement a standardised behaviour change communication intervention strategy (BCC) and to measure its impact on the population in terms of awareness, attitude and practice regarding dengue and its vector control. Methods: This study was carried out in a ward in Njarackal Panchayath in Ernakulam district of Kerala. An initial baseline survey was conducted to assess the current awareness, attitude and practices of dengue & its vector control among the residents of the ward. This was followed by the implementation of standardized BCC Intervention strategy. A post intervention survey was carried out two months later to analyze its impact. Results: This BCC strategy resulted in increasing the awareness regarding dengue and its vector control even though it was found not to be statistically significant. However, the strategy was able to bring about a significant change in the attitude and practice of the people with regard to dengue prevention and control strategies. Conclusions: This BCC strategy was successful in this population due to community acceptance, however it requires constant reinforcement for its sustainability.